The role of reinforced carbon fiber plates in supracondylar femoral fractures - Tartaglia, Nicola; Giorgio, Alessandro; Saracino, Michele (Lo Scalpello - Journal, 2021)
One of the surgical options for the supracondylar femoral fractures is plating. These fractures are often unstable because of many factors depending on the type of fracture (medial wall often involved) and quality of bone (osteoporosis). Supracondylar lateral plates, even if provided by long plates and good distribution of screws, may fail because of high mechanical stress. In fact, in the literature a non-union rate 21% of is described. PEEK materials are already used regularly in pathological fractures where better mechanical properties are required where the callogenesis is often slow and uncomplete because of pathological healing process. Since 2016, the authors used these better mechanical properties (biocompatibility, resistance and elasticity) of PEEK plates in selected trauma cases in the supracondylar femoral site. Among the few cases successfully treated with lateral PEEK plate, the authors report one peculiar case with 3 years of follow-up highlighting the good properties of reinforced carbon fibers.